IMPLEMENTATION OF ISBAT NIKAH SOCILIZATION IN RESOLVING UNREGISTERED MARRIAGE REGISTRATION ISSUE (A STUDY AT THE RELIGIOUS COURT OF RANGASBITUNG) - Utari Nurhalizah; Hilman Taqiyudin; Tb. Ahmad Mahdi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study investigates the issue of unregistered marriages in Lebak Regency, which persists due to low public legal awareness, the widespread practice of unregistered (siri) marriages, and various access barriers such as financial constraints and geographical distance from civil registration offices. These circumstances lead to significant legal uncertainty for families, particularly concerning lineage status, inheritance rights, and children's educational entitlements. The research aims to examine the effectiveness of the isbat nikah (marriage legalization) outreach program implemented by the Rngkasbitung Religious Court and to formulate recommendations for enhancing formal marriage registration and strengthening legal protection for the community. Employing a qualitative case study approach, data were collected through interviews with court clerks, partner institutions, and local residents, as well as through document analysis of isbat nikah cases from 2023 to 2025. June 2025. However, persistent challenges remain, particularly the community's pragmatic attitudes and limited institutional infrastructure, which continue to impede the program's optimal implementation.